2019
DOI: 10.1177/1479164119860746
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum FAM19A5 with metabolic and vascular risk factors in human subjects with or without type 2 diabetes

Abstract: Objectives: A recent experimental study revealed that family with sequence similarity 19 [chemokine (C-C motif)-like] member A5 (FAM19A5), a novel secreted adipokine, has inhibitory effects on vascular smooth muscle cell proliferation and migration, and on neointima formation in injured arteries. We investigated the associations between serum FAM19A5 concentration and cardio-metabolic risk factors for the first time in human subjects. Methods: Circulating FAM19A5 concentrations and their associations with card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 28 publications
1
24
1
Order By: Relevance
“…Intriguingly, FAM19A5 mRNA and protein levels are significantly down-regulated in obese and diabetic animals 3 , suggesting a causal relationship between decreased FAM19A5 levels and metabolic disease conditions. However, this result is in part contradictory to a recent observation in humans where individuals with type 2 diabetes had higher FAM19A5 serum levels than those without type 2 diabetes 9 . The public database for human tissue RNA expression reports that FAM19A5 is expressed in the female and male reproductive tissues including the ovaries, uterus, and testis, although absolute levels in these tissues are significantly lower than brain tissue levels 4,10 .…”
Section: Introductioncontrasting
confidence: 99%
“…Intriguingly, FAM19A5 mRNA and protein levels are significantly down-regulated in obese and diabetic animals 3 , suggesting a causal relationship between decreased FAM19A5 levels and metabolic disease conditions. However, this result is in part contradictory to a recent observation in humans where individuals with type 2 diabetes had higher FAM19A5 serum levels than those without type 2 diabetes 9 . The public database for human tissue RNA expression reports that FAM19A5 is expressed in the female and male reproductive tissues including the ovaries, uterus, and testis, although absolute levels in these tissues are significantly lower than brain tissue levels 4,10 .…”
Section: Introductioncontrasting
confidence: 99%
“…Wang et al showed FAM19A5 inhibits the vascular smooth muscle cells proliferation and ameliorates neointima formation in the injured rat carotid arteries (8). Although several studies addressed contribution of FAM19A5 to neurological disorders (19)(20)(21)(22)(23), existing data on a relevant association of FAM19A5 and cardiac and metabolic disorders are very limited (8,9). To our knowledge, this is the first clinical observation pointing to the association of FAM19A5 with the pathogenesis of NAFLD.…”
Section: Introductionmentioning
confidence: 81%
“…These results are in agreement with our ndings which showed lower circulating levels of FAM19A5 in NAFLD. However, Lee et al reported higher serum levels of FAM19A5 in diabetic patients compared to nondiabetic subjects (9). These inconsistent ndings might be related to the different inclusion and exclusion criteria used in various human studies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations